Interference of mycobacterium tuberculosis with the endocytic/ antigen presentation pathways on macrophages and dendritic cells - Pires, David (2016)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2014